Late Embryogenesis Abundant (LEA) proteins in legumes - Battaglia, Marina; Covarrubias, Alejandra A. (Frontiers in Plant Science, 2013)
Plants are exposed to different external conditions that affect growth, development, and productivity. Water deficit is one of these adverse conditions caused by drought, salinity, and extreme temperatures. Plants have developed different responses to prevent, ameliorate or repair the damage inflicted by these stressful environments. One of these responses is the activation of a set of genes encoding a group of hydrophilic proteins that typically accumulate to high levels during seed dehydration, at the last stage of embryogenesis, hence named Late Embryogenesis Abundant (LEA) proteins. LEA proteins also accumulate in response to water limitation in vegetative tissues, and have been classified in seven groups based on their amino acid sequence similarity and on the presence of distinctive conserved motifs. These proteins are widely distributed in the plant kingdom, from ferns to angiosperms, suggesting a relevant role in the plant response to this unfavorable environmental condition. In this review, we analyzed the LEA proteins from those legumes whose complete genomes have been sequenced such as Phaseolus vulgaris, Glycine max, Medicago truncatula, Lotus japonicus, Cajanus cajan and Cicer arietinum. Considering their distinctive motifs, LEA proteins from the different groups were identified, and their sequence analysis allowed the recognition of novel legume specific motifs. Moreover, we compile their transcript accumulation patterns based on publicly available data. In spite of the limited information on these proteins in legumes, the analysis and data compiled here confirms the high correlation between their accumulation and water deficit, reinforcing their functional relevance under this detrimental conditions.